2022
DOI: 10.1021/acs.jpca.1c10717
|View full text |Cite
|
Sign up to set email alerts
|

Potential Matrix Effects in Iodometry Determination of Peroxides Induced by Olefins

Abstract: Peroxides (H 2 O 2 , ROOR, and ROOH) are an important reaction intermediate involved in a number of natural processes, including atmospheric autoxidation and lipid peroxidation in oils and animal tissues. Iodometry is an established spectroscopic technique that has been widely used to quantify total peroxide concentration in food, indoor, and outdoor samples. Iodometry provides selectivity toward peroxides through a quantitative reaction between I − and peroxides to form I 3 − via a molecular iodine (I 2 ) int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 117 publications
0
13
0
Order By: Relevance
“…As indicated in Figure , most of the PO measurement assays (e.g., the KI, TPP, and DCFH methods) are suitable for bulk PO quantification only, with uncertainties arising from different sample preparation procedures across different laboratory studies. Recently, a potential matrix effect in the KI assay has been reported that underestimation of the peroxide content could occur with the interference from olefins (structurally dependent) in the system . Although the interference from alkenes is likely to be unimportant because of their low sensitivity and low typical concentrations in organic aerosol, such findings emphasize a careful interpretation of the KI-measured PO content in olefin-rich systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As indicated in Figure , most of the PO measurement assays (e.g., the KI, TPP, and DCFH methods) are suitable for bulk PO quantification only, with uncertainties arising from different sample preparation procedures across different laboratory studies. Recently, a potential matrix effect in the KI assay has been reported that underestimation of the peroxide content could occur with the interference from olefins (structurally dependent) in the system . Although the interference from alkenes is likely to be unimportant because of their low sensitivity and low typical concentrations in organic aerosol, such findings emphasize a careful interpretation of the KI-measured PO content in olefin-rich systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a potential matrix effect in the KI assay has been reported that underestimation of the peroxide content could occur with the interference from olefins (structurally dependent) in the system. 294 Although the interference from alkenes is likely to be unimportant because of their low sensitivity and low typical concentrations in organic aerosol, such findings emphasize a careful interpretation of the KI-measured PO content in olefin-rich systems. Additionally, some of the assays may be more sensitive to specific peroxides than to others, and therefore care must be taken in interpreting the PO quantification results.…”
Section: Detection Of Posmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic peroxides are strong oxidants which have been utilized in the analysis of peroxides. 158 The iodometric reactions have good specificity for peroxides, and the reactions are fast enough for quantitative analysis applications, although the substituents attached to the peroxide groups have an effect on the speed of the reaction. For example, a tert -butyl group in the molecule has been demonstrated to slow down the reaction as the group causes steric hindrance and possibly an inductive effect that stabilizes the peroxide group.…”
Section: Analytical Methods For Oxidized Compounds In the Atmospherementioning
confidence: 99%